Scoping review of cytolytic vaginosis literature. - Roni Kraut; Fabiola Diaz Carvallo; Richard Golonka; Sandra M Campbell; Anoush Rehmani; Oksana Babenko; Mao-Cheng Lee; Pedro Vieira-Baptista (PLoS ONE)
Background Cytolytic vaginosis (CV) is a little-known, controversial condition that is typically not considered for women presenting with vulvovaginitis symptoms. Objective: The objective of this scoping review was to identify and compile the global evidence on CV. Methods A medical librarian searched Prospero, Wiley Cochrane Library, Ovid Embase, Ovid Medline, EBSCO CINAHL, ProQuest Dissertations and Theses Global, and Scopus, from inception to April 4, 2019 and updated to October 17, 2021. Studies were eligible if they discussed CV. Two independent reviewers conducted study selection and data extraction. Results Sixty-four studies were identified, with 67% of studies (n = 43) published since 2007. Studies were from around the world, including the United States (28%, n = 18), Brazil (11%, n = 7), Portugal (11%, n = 7), and China (11%, n = 7). Fifty percent of studies (n = 32) were reviews; the remainder were observational; and of these, 78% (n = 25) were cross-sectional. The most frequent topics included: diagnosis (19%, n = 12), prevalence (17%, n = 11), and overview of CV (50%, n = 32). Evidence for prevalence in symptomatic women (median prevalence of 5%, interquartile range 3%-8%) was based only on 16% of studies (n = 10) with minimal evidence on prevalence in asymptomatic women and across different geographic regions. Microbiological findings, including abundant lactobacilli and fragmented epithelial cells, were found useful to distinguish between CV and vulvovaginal candidiasis, and Lactobacillus crispatus was noted to dominate the vaginal flora in women with CV. Most studies used subjective criteria to diagnose CV as the condition lacks gold-standard microscopic criteria. The suggested primary treatment (baking soda irrigations) was largely based on expert opinion, and there was minimal evidence on associations between CV and other conditions. Conclusion Knowledge gaps currently exist in all realms of CV research. Additional research is needed to confirm the validity of CV and ensure that women are diagnosed and treated effectively.